Translational error in mice increases with ageing in an organ-dependent manner - Erik C. Böttger; Harshitha Santhosh Kumar; Adrian Steiner; Emmanuel Sotirakis; Kader Thiam; Patricia Isnard Petit; Petra Seebeck; David P. Wolfer; Dimitri Shcherbakov; Rashid Akbergenov (Nature Communications)
Abstract The accuracy of protein synthesis and its relation to ageing has been of long-standing interest. To study whether spontaneous changes in the rate of ribosomal error occur as a function of age, we first determined that stop-codon readthrough is a more sensitive read-out of mistranslation due to codon-anticodon mispairing than missense amino acid incorporation. Subsequently, we developed knock-in mice for in-vivo detection of stop-codon readthrough using a gain-of-function Kat2-TGA-Fluc readthrough reporter which combines fluorescent and sensitive bioluminescent imaging techniques. We followed expression of reporter proteins in-vivo over time, and assessed Kat2 and Fluc expression in tissue extracts and by whole organ ex-vivo imaging. Collectively, our results provide evidence for an organ-dependent, age-related increase in translational error: stop-codon readthrough increases with age in muscle (+ 75%, p < 0.001) and brain (+ 50%, p < 0.01), but not in liver (p > 0.5). Together with recent data demonstrating premature ageing in mice with an error-prone ram mutation, our findings highlight age-related decline of translation fidelity as a possible contributor to ageing.